2020
DOI: 10.1021/acsabm.0c00860
|View full text |Cite
|
Sign up to set email alerts
|

Co-Axial Fibers with Janus-Structured Sheaths by Electrospinning Release Corn Peptides for Wound Healing

Abstract: Delayed wound healing in skin is strongly correlated with excessive reactive oxygen species (ROS) generation. Corn peptides (CPs) have robust antioxidant and anti-inflammatory effects. Therefore, the study sought to evaluate the wound healing effect of topical application of CPs embedded in wound dressings fabricated using the coaxial electrospinning technique. A special structure, which was a co-axial structure with a Janus-structured sheath, was displayed on the fiber. The fibers exhibited stable thermal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 51 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…1D) clearly showed a cracked surface and hollow inside (yellow arrows), which is attributed to the different surface properties of the Janus nanofibers as our previous research reported. 32,33 Briefly, after soaking in water, the hydrophobic PCL component of the nanofibers remained intact and the hydrophilic PVP component was degraded. 002), ( 112), ( 022), (013), and (222), indicating that the ZIF-8 NPs were dispersed in the nanofibers.…”
Section: Characterizations Of the Janus Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…1D) clearly showed a cracked surface and hollow inside (yellow arrows), which is attributed to the different surface properties of the Janus nanofibers as our previous research reported. 32,33 Briefly, after soaking in water, the hydrophobic PCL component of the nanofibers remained intact and the hydrophilic PVP component was degraded. 002), ( 112), ( 022), (013), and (222), indicating that the ZIF-8 NPs were dispersed in the nanofibers.…”
Section: Characterizations Of the Janus Nanofibersmentioning
confidence: 99%
“…31 In our previous study, we produced Janus nanofibers taking advantage of the phase separation in polycaprolactone (PCL) and polyvinylpyrrolidone (PVP) solution by uniaxial electrospinning. 32,33 PCL is a biodegradable polymer with good mechanical properties, the hydrophobic nature of which allows the cargo to be released continuously. 34,35 PVP is a synthetic water-soluble polymer that has been applied as a fastdissolving matrix carrier in various drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, emulsion electrospinning involves two immiscible phases of polymers and a therapeutic agent, whereby the agent can be encapsulated throughout the nanofibers matrix or encapsulated in the core-shell nanofibers [ 131 , 132 , 133 ]. Co-axial electrospinning uses two nozzles containing the polymer solution and the therapeutic agent separately, to produce a core-shell structure in the nanofibers [ 134 , 135 , 136 , 137 ]. Usually, the polymer matrix will provide the outer core, while the therapeutic agent is incorporated in the inner core of the nanofibers [ 27 , 138 ].…”
Section: Polymeric Nanofibers and Electrospun Scaffoldsmentioning
confidence: 99%
“…[24][25][26] These dressings have ductility and tensile strength comparable to human skin, so they can t the wound well. 27 Meanwhile, the electrospinning nanober membrane also has the characteristics of the three-dimensional support structure, small pore size and high surface area to volume ratio. 28 To a certain extent, the designed electrospinning nanober membranes can be used to simulate the biological functions of extracellular matrix (ECM) and provide an ideal microenvironment for cell adhesion, proliferation and further differentiation.…”
Section: Introductionmentioning
confidence: 99%